Students on farm : activities, careers and partnerships in lamb and sheepmeat - Bodi, Anna, 1954- (CWCC ; Meat and Livestock Australia, 2003)
Addresses problems of attracting young people to the lamb and sheep meat sector of agriculture as part of identifying labour and skill issues being underlying factors in continuing growth for the industry.